Coccidioidomicose no estado do Ceará : caracterização protéica, descrição de microepidemia, virulência in vivo e potencial imunoprotetor de antígeno isolado de Coccidioides posadasii - Moreira Filho, Renato Evando (2012)
Scientific researches seeking to use Coccidioides posadasii antigens are common in the literature, as relevant instruments to diagnosis and possible immunoprotector effect in humans. Thus, we performed biochemical characterization of protein antigen derived from C. posadasii, an active search for human cases of coccidioidomycosis in Ceará, as well as evaluation of immune response in vivo. To achieve these goals, the biochemical characterization of the antigen was performed by electrophoresis (SDS-PAGE and 2D-PAGE), detection of proteases, glycoproteins and N-terminal sequencing and we reported three human cases of coccidiodiomycosis in armadillo hunters with its clinical description and laboratory evaluation. Further, a murine model was described testing a possible imunoprotector effect with an in-house antigen. For biochemical analysis, it was observed delimitation bands in ranges 45-67 kDa and 67-97 kDa (SDS-PAGE), detection of glycoproteins, proteases and N-terminal sequencing demonstrating the bands being a β-glucosidase and a glutamine synthetase. In clinical cases, it was found pneumonic disease, direct mycological examination, sputum culture, double radial immunodiffusion (antigen in-house) and PCR positive for C. posadasii. In the murine model, the infected group, in the presence of antigen and adjuvant, showed, histologically, lung disorders smaller than the other groups, and increased splenic lymphoid stimulus. Regarding the cytokines (IL-6, IL-12 and TNF), there was no significant difference between groups, but a trend toward immunoprotective response. The infected group, without immunoprotection, showed greater weight loss. In the macroscopic analysis, the maximum commitment was the presence of 2 granulomas in the latter group. In the analysis of blood counts, the white run showed major differences between groups. In conclusion, the in-house antigen showed that it was a β-glucosidase and a glutamine synthetase which tended to stimulate cellular immunity in a murine model. Moreover, the description of human cases contributes to the spread of early diagnosis of coccidioidomycosis and requires additional laboratory investigations.